Hydraulic Flow Unit Characterization in Sandstone Reservoirs, Niger Delta, Nigeria - Nwokoma, Esomchi U.; Ijeh, Boniface I.; Amos-Uhegbu, Chukwunenyoke (Earth and Planetary Science, 2023)
The key factor in a successful oil field development plan is understanding the reservoir. The effectiveness of oil extraction is determined by variations in the reservoir, specifically the distribution of porosity and permeability. To create an accurate model of the reservoir, the vertical distribution of its qualities must be determined and separated into flow units, each with its own unique characteristics that affect fluid flow. By identifying these flow units, the preferred flow zones can be discovered. The aim of this study is to identify the number and distribution of hydraulic units, their important characteristics, and the flow performance in two specific wells in the Niger Delta, Nigeria, using the Modified Lorenz Plot (MLP) method. In the hydrocarbon-rich intervals of the wells, a total of 18 flow units were found, with 12 in Well 1 and 6 in Well 2. The number of flow units indicates the level of heterogeneity in the reservoir. This study showed that the Modified Lorenz Plot (MLP) is an efficient and low-cost method for defining petrophysical flow units. This research study aims to transform the conventional approach to reservoir characterization by conducting a thorough analysis of hydraulic flow units in sandstone reservoirs located in the complex geological setting of the Niger Delta, Nigeria. By examining the hydraulic properties of reservoir rocks, the study seeks to gain a better understanding of subsurface fluid flow behavior and the potential for hydrocarbon accumulation. ER